The efficacy of conservation practices in reducing floods and improving water quality - Srivastava, Shivendra; Basche, Andrea; Traylor, Elbert; Roy, Tirthankar (Frontiers in Environmental Science, 2023)
Conservation practices such as crop rotation, filter strips, and constructed wetlands are nature-based approaches intended to safeguard natural resources in agricultural landscapes. In this study, we reviewed the literature on how conservation practices, both at watershed and field scales, have been proven to subdue flood peaks, surface runoff, soil erosion, sediment transport, and nutrient loss. We classified different conservation practices based on the mode of their application (i.e., in-field, edge-of-field, and structural practices) and described what prior research efforts have concluded about the efficacy of different practices. At the field scale, practices such as reduced or no-till farming, grassed waterways, and creation of wetlands significantly reduced the peak flow. Similarly, water quality was improved with implementation of conservation practices such as using cover crops, filter strips, and managing residue and tillage. The assessment of conservation practices across the literature was found to be challenging as different conservation practices showed a similar response, thus making it complex to assess the individual effect. A wide range of challenges related to the data, modeling/analysis, and management aspects of conservation practices were identified, and recommendations were provided to overcome these challenges.